Oral And Maxillofacial Manifestations Of Covid-19 - Integrative Literature Review - Nathália Luise Severo Reis; Nathalia Rosa Nascimento Domingos; Marcus Antônio Brêda Júnior; Dayse Andrade Romão (Portal de Periódicos da Marinha do Brasil, 2023)
Scientific evidence suggests that SARS-CoV-2 is present in the oral tissues in the initial phase of contamination as the main viral reservoir. Besides the oral cavity being the main means of spread, it also becomes a common location of clinical manifestations during the onset and evolution of the disease. The objective was to evaluate the literature about the oral and maxillofacial clinical manifestations arising from Covid-19 contamination. This is an integrative literature review of the databases Latin American and Caribbean Literature on Health Sciences (Lilacs), Scientific Electronic Library Online (Scielo) and BBO Dentistry, of articles published between 2019 and 2022 that portrayed the theme of the study. Initially, the search for the descriptors was conducted individually, then, the crossings were performed using the Boolean operator "AND" and, subsequently, the three descriptors were crossed together. The inclusion criteria were articles published in Portuguese, English and Spanish, published and indexed in the databases, starting in 2019 - year of the emergence of Covid-19 and that portrayed the theme of the study. The exclusion criteria were articles published before 2019, articles outside the chosen databases, and articles that ran away from the theme of the study. During the study, 28 articles were selected from all the cited criteria. It was concluded that patients contaminated with Covid-19 had oral and maxillofacial clinical manifestations that may include ulcerations, inflammation in the oropharynx, retromandibular edema, fungal infections, xerostomia, anosmia, and ageusia.